Knowledge of and Attitudes towards Preventive Dental Care among Iranian Dentists - Ghasemi, Hadi, DDS; Murtomaa, Heikki, DDS, PhD, MPH; Torabzadeh, Hassan, DDS, MSc, PhD; Vehkalahti, Miira M, DDS, PhD (European Journal of Dentistry, 2013)
Objectives: To assess Iranian dentists’ knowledge of and attitudes towards preventive dental careMethods: A questionnaire survey was conducted at two nationwide annual dental congresses in 2004 and 2005 in Tehran, Iran. Dentists’ level of knowledge was assessed based on their responses on a Likert scale (0-4) to nine statements on preventive dental care. Higher scores indicated more accurate knowledge. Dentists’ attitudes towards preventive dental care were rated based on responses on a Likert scale (1-7) to nine pairs of bipolar adjectives. The respondents were to choose the response which best described their opinion. Higher scores indicated more positive attitudes. Of 1033 responding dentists, 980 (64% men) were deemed eligible for this study. Statistical evaluation was by t-test and the Chi-square testResults: Highest ratings were obtained for knowledge of the role of sugar consumption (Mean±SD: 3.73±0.60), sealants (3.58±0.68), and water fluoridation (3.35±0.81) in caries prevention; the lowest for their knowledge of the superiority of the use of fluoride toothpaste over technique of brushing (1.11±1.09). Dentists’ attitudes towards preventive dental care appeared most positive regarding its usefulness (Useful — Useless; 6.67±0.94), value (Valuable — Worthless; 6.59±0.98) to the community and for its status as a scientific (Scientific — Unscientific; 6.47±1.06) subject. Overall, female dentists had more favourable attitudes towards preventive dental care than male colleaguesConclusions: Preventive dentistry should be emphasised in dental education in order to update dentists’ knowledge and attitudes regarding preventive dental care. (Eur J Dent 2007;1:222-229)
Keywords: Preventive dentistry; Dental care; Iranian Dentists; Dental Education